Exit and Voice The Paradox of Cross-Border Politics in Mexico - Duquette-Rury, Lauren (University of California Press, 2020)
"Exit and Voice is a compelling account of how Mexican migrants with strong ties to their home communities impact the economic and political welfare of those they leave behind. In many decentralized democracies like Mexico, migrants step in to supply public goods when local or state government cannot. Though migrants' cross-border investments often improve citizens' access to these goods and create a more responsive local government, their work allows them to unintentionally exert political engagement and power, undermining the influence of those still living in their hometowns. Exit and Voice sheds light on how migrant transnational engagement refashions the meaning of community, democratic governance, and practices of citizenship in the era of globalization. "An extraordinary analysis of what it means to be a migrant. Duquette-Rury gives us a text that goes well beyond the familiar, and situates the migrant in a complex set of vectors, both local and transnational, opening up the meaning of migration itself." SASKIA SASSEN, author of Expulsions: Brutality and Complexity in the Global Economy "How do people who move to another country sometimes become more influential in the place they left? Exit and Voice combines surveys and lively details from original fieldwork to explore this paradox and identify the fragile pillars sustaining efforts to live in two worlds." DAVID FITZGERALD, author of Refuge beyond Reach: How Rich Democracies Repel Asylum Seekers "Despite distance and difficulties, migrants around the world reach down into their pockets to help out the communities they left behind. Hoping that migration can spur development and possibly even democracy, scholars and policy makers find the effort laudable. But as Duquette-Rury demonstrates in this brilliant, beautifully written book, engaging from abroad is a challenging enterprise. A book to be savored by scholars and students alike." ROGER WALDINGER, Distinguished Professor and Director of the UCLA Center for the Study of International Migration"